Inactivation of Fusarium oxysporum Conidia in Soil with Gaseous Ozone–Preliminary Studies (2020)
In this study, the efficiency of gaseous ozone (O3) injected in the soil as an oxidizing agent for the inactivation of F. oxysporum was evaluated under laboratory conditions. The results show the treatment reached an inactivation efficiency of 76% after an applied dose of 0.40 g O3 kg ?1 soil. This shows that the injection of O3 can be a viable alternative to control pathogenic organisms in the soils. Nevertheless, it is clear that more studies on determining the effects of this treatment on soil quality are needed. © 2019, © 2019 International Ozone Association.